Different tryptophan-kynurenine metabolism profiles in human pulmonary arterial hypertension and animal models of pulmonary hypertension. (25th November 2020) - Cai, Z; Klein, T; Tu, L; Geenen, L.W; Tian, S; Van Der Ley, C; Van Faassen, M; Kema, I; Van Den Bosch, A.E; De Rijke, J.B; Reiss, I.K.M; Duncker, D.J; et al.
Abstract: Background: De novo NAD+ synthesis through the tryptophan-kynurenine (TK) metabolism was recognized as an important pathway in improving mitochondrial function and survival of injury or apoptotic cells, which are key processes involved in the pathogenesis of pulmonary arterial hypertension (PAH). Although abnormal TK metabolism has been reported in human PAH, the difference between human and animal models of pulmonary hypertension (PH) are currently unknown. Objective: Determine and compare TK metabolism profiles in plasma from human PAH and 3 animal models of PH. Methods: Human plasma was collected from treatment naïve patients with PAH (n=43) and healthy controls (n=111). Animal plasma was collected from 3 animal models of PH and corresponding controls, including monocrotaline (MCT) induced PH in rat (n=7, control n=6), Sugen + hypoxia (SuHx) induced PH in rat (n=5, control n=6), and pulmonary vein banding (PVB) induced PH in swine (n=7, control n=6). TK metabolites were determined using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: TK metabolism was altered in the plasma from of PAH compared to healthy controls (Figure 1A). Lower tryptophan (0.8 fold vs Control, p<0.0001), maintained 3-hydroxyanthranilic acid, and higher kynurenine, 3-hydroxykynurenine, anthranilic acid, and quinolinic acid (1.5, 2.6, 2.0, 2.6 fold vs Control, respectively, p all<0.0001) were seen in the plasma from human PAH. In the rat SuHx-PH model, kynurenine (0.7 fold, p<0.01) and quinolinic acid (0.5 fold, p<0.001) were lower, while 3-hydroxyanthranilic acid (4.3 fold, p<0.001) was higher in PH compared to control (Figure 1B). However, the TK metabolism was unaltered in MCT-PH model in rat (Figure 1C), and PVB-PH model in swine (Figure 1D). Conclusions: TK metabolism was altered in the plasma from human PAH. The TK metabolism profiles were different among 3 animal models of PH, but did not mimic the profile in human PAH. Further research is required to determine the mechanism(s) behind the abnormal TK metabolism in human PAH as well as whether these mechanisms relate to disease onset or progression. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): This work was supported by the China Scholarship Council (201606230252) as well as the Netherlands CardioVascular Research Initiative: an initiative with support of the Dutch Heart Foundation (CVON2014-11, RECONNECT), and German Center for Cardiovascular Research (DZHK81Z0600207). Instrumentation support was received from AB Sciex, ltd. for LC-MS/MS analyses performed in this study.